Warm Blood Retrogrades Coronary Sinus Perfusion in Beating Heart Technique for Aortic Valve Replacement in 73 Cases - Maghaiya, Durgendra Bikram; Shamsi, Bilal Haider; Min, Geng Zhi; Yang, Yan (Cardiology and Cardiovascular Medicine, 2017)
Purpose: Explore the clinical value of warm blood retrograde coronary sinus perfusion in beating heart for aortic valve replacement surgery. Methods: Clinical retrospective analysis of 73 patients with warm blood retrograde coronary sinus perfusion in beating heart method is used for aortic valve replacement surgery. Results: No death in all 73 cases with method of warm blood retrograde coronary sinus perfusion in beating heart for aortic valve replacement surgery. There was no severe arrhythmia, given a small amount of vasoactive drugs and no death occurred in 71 cases with postoperative follow-up for one year, and all the patients recovered well. Conclusion: Method of warm blood retrograde coronary sinus perfusion in beating heart for aortic valve replacement surgery can be effective in preventing more damage to myocardial lesion, greatly reduce postoperative low cardiac output syndrome and severe arrhythmias, compared to traditional methods of myocardial protection.